Nanoparticles for drug delivery: Insight into in vitro and in vivo drug release from nanomedicines - Ugochi E. Ewii; Anthony A. Attama; Emmanuel O. Olorunsola; Adaeze Linda Onugwu; Fortune Uchechukwu Nwakpa; Chioma Anyiam; Chinonye Chijioke; Toochukwu Ogbulie (Nano TransMed)
Nanotechnology enables the achievement of the desired outcomes of nano-formulations, and the mode of drug delivery from the nanoparticles can significantly impact the efficacy of the embedded drug. This article reviews the various types of nanoparticles, methods of evaluating the drug release, in vitro-in vivo correlation, and regulatory challenges associated with nano-formulations. Nanoparticles have been classified into organic, inorganic, and hybrid nanoparticles. Several techniques, such as separated flow, continuous flow, and dialysis methods, have been utilized to assess nano-formulations' in vitro release. In vivo drug release evaluations in biological systems have also been demonstrated. Such evaluations often involve experimental models for the distribution of the nanoparticles, hematology, clearance, histopathology, and serum chemistry. Protein binding, enzymatic degradation, lipid absorption, carbohydrate absorption, and attachment to nucleic acid are some factors shown to affect drug release. In vitro-in-vivo correlation (IVIVC) involves the analysis of the drug release results and mathematical correlations. Factors such as the physicochemical properties of the nanoformulations, the subject’s physiological properties, and the formulation’s biopharmaceutical properties relative to the subject usually affect the correlation. Unlike previous reviews, this article uniquely combines mechanistic insights, production methods, stimuli-responsive systems, and regulatory considerations into a single reference, thereby offering a practical and translational perspective for researchers and formulators. This review also identifies current gaps in IVIVC standardization and highlights opportunities for advancing nanoformulation safety and efficacy.